PENGARUH PENGGUNAAN METODE EKSPERIMEN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DI KELAS V SD NEGERI 101790 MARINDAL II KECAMATAN PATUMBAK - Rinci Simbolon; Winda sahpitri br sitepu (JURNAL CURERE, 2019)
The problem in this research is the result of student learning has not been fullest. The purpose of this research is to know the results of student learning and influence the use of experimental methods towards learning outcomes students on subjects natural science material properties of light in class V 2017/2018 academic year.This type of research is quasi experiment. This research is carried out in SD Negeri 101790 Marindal II Patumbak Sub-district. The population of this research is the whole grade V SD Negeri 101790 Marindal II Patumbak Sub-district of 51 students all at once into the research sample is divided into two parallel classes. Data collection tool used is a form of test and analysis of the data used is test, test of its homogeneity and normality and hypothesis testing to use independent test between two factors.Data analysis of the results obtained that the results of student learning on subjects natural science Material properties of light are not the same after using the experimental method in the class V SD Negeri 101790 Marindal II Patumbak Sub-district, the values obtained the average student learning outcomes and 76.80 on subjects natural science material properties of light are not the same increased after using conventional learning in class V SD Negeri 101790 Marindal II Patumbak Subdistrict, obtained average value of 62.42. And the results of student learning on subjects natural science material properties of light using experimental methods better than using conventional learning in class V SD Negeri 101790 Marindal II 2017/2018 Patumbak Sub-district